(untitled) (Revista de Investigaciones Universidad del Quindío, 2010)
A descriptive analysis was carried out about health conditions of workers exposed to wood dust in the areas of sanding, planing and painting (this kind of workers are most likely to suffer respiratory problems or illness from exposure to wood dust). Given the similarity of tasks, materials and equipment used, we took ten of the representative companies in Quindío as the control group. The study surveyed 100% of workers in the above areas. 22.6% tested positive for respiratory problems, and these workers were chosen for the development of occupational medical records. We identified the use of hardwoods and softwoods in furniture making; immunization agents or pesticides; volatile organic solvents; synthetic epoxy resins; adhesives and paints for wood finishes. Of the total respondents, 45% were women (all of whom where heads of households), and 55% men. The average age was 31 years, with the youngest 19 years, and the eldest 51 years old. With regard to personal health habits, 20% are smokers and 45% drink alcohol. 45% play sports and 100% denied suffering any occupational disease. 100% of workers complained of suffering from coughs, hoarseness, rhinitis, conjunctivitis and frequent colds. A notable lack of healthy lifestyles and epidemiological surveillance company programs (together with the environmental conditions in their areas of work) generate a significant risk factor for chronic health events, such as obstructive lung disease (COPD).